Marble Industry Sentra Design In South Aceh Regency - Resky Rusnanda; Oktalia Triananda Lovita (Jurnal Inotera, 2018)
Indonesia has a variety of crops, especially in the field of rocks, some of which are famous to the corners of the world one of them is Marble Stone. Kabupaten Aceh Selatan, is also one of the marble-producing locations in Aceh Province. Tapaktuan sub-district is one of marble stone processing center in South Aceh regency. The location of marble processing in Tapaktuan City is currently located at UPT Marmer Polytechnic of South Aceh campus. Processing industry in UPT marble Poltas are included in medium scale industries which use tools with large capacity and sufficient for processing of marble stone. However, there are some problems that arise due to the activity of marble pegolahan. Among them, the occurrence of environmental pollution derived from the process of making marble handicrafts. Waste generated from cutting, smelting, polishing, resulting in a solution of water mixed with lime which is a problem for the environment, as well as disturbing the surrounding community for causing noise and pollution. The purpose of this research is to produce the design of industrial center of marble in South Aceh regency applying the concept of Suistanable Arichitectur, which can reduce the impact of natural damage due to the processing of marble stone. The method used is the concept of Suistanable Architecture. The results of this study include the design of lanskape central marble industry.